ОЦІНКА РУХОВОЇ АКТИВНОСТІ ШКОЛЯРІВ В УМОВАХ ПАНДЕМІЇ COVID-19 - Дмитроца, О. Р.; Коржик, О. В.; Журавльов, О. А. (Українські медичні вісті, 2023)
ОЦІНКА РУХОВОЇ АКТИВНОСТІ ШКОЛЯРІВ В УМОВАХ ПАНДЕМІЇ COVID-19